New insights into structural, optical, electrical and thermoelectric behavior of Na0.5Bi0.5TiO3 single crystals - G. Jagło; Kamila Kluczewska-Chmielarz; J. Suchanicz; A. Kruk; A. Kania; D. Sitko; M. Nowakowska-Malczyk; M. Łapiński; G. Stachowski (Scientific Reports)
Abstract The single crystals of lead-free Na0.5Bi0.5TiO3 were grown using the Czochralski method. The energy gaps determined from X-ray photoelectron spectroscopy (XPS) and optical measurements were approximately 2.92 eV. The current-voltage characteristics, depolarization current, dc (σdc) and ac (σac) electrical conductivity, and Seebeck coefficient of the crystals were investigated. The frequency/temperature-dependent electrical properties were also measured and analyzed through complex impedance spectroscopy. An overlapping reversible insulator-metal transition (resistive switching) on nanoscales, caused by the electric field, was detected. Most of these properties were measured for the first time. The activation energy values determined from the conductivity data, the imaginary part of the electric impedance and the modulus indicate that the relaxation process in the high-temperature range is attributable to both single and double ionized oxygen vacancies, in combination with the hopping of electrons between Ti4+ and Ti3+. P-type electrical conductivity was also found. These discoveries create new possibilities of reducing the electrical conductivity of NBT and improving the process of effectively poling this material. Our results indicate the possibility of tuning the material properties by intentionally creating non-stoichiometry/structural defects (oxygen vacancies, cation excess and cation deficiency).